Adaptive memory: Stereotype activation is not enough - Otgaar, Henry (Springer-Verlag, 2011)
Studies have shown that survival processing leads to superior memorability. The aim of the present study was to examine whether this survival recall advantage might result from stereotype activation. To test this hypothesis, we conducted a pilot study and two experiments in which participants were primed with stereotypes (Experiment 1, professor and elderly person; Experiment 2, survival-stereotype). In Experiment 1, 120 undergraduates were randomly assigned to a survival, professor stereotype, elderly person stereotype, or moving scenario and rated words for their relevance to the imagined scenario. In Experiment 2, 75 undergraduates were given a survival, survival-stereotype (based on our pilot study), or moving scenario. Both experiments showed that survival processing leads to a greater recall advantage over the stereotype groups and control group. These data indicate that the mere activation of stereotypes cannot explain the survival recall advantage.